2005
DOI: 10.1002/hipo.20045
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal-dependent memory is impaired in heterozygous GAP-43 knockout mice

Abstract: Cajal proposed that the rearrangement and growth of neurites and synaptic terminals is a substrate for the formation and storage of long-term memories. Proteins that regulate this learning-dependent growth are therefore likely to be "core determinants" (Sanes and Lichtman, Nat Neurosci 1999; 2:597-604) of such information storage processes. Although the growth-associated, protein kinase C (PKC) substrate GAP-43 has been oft-implicated in synaptic plasticity and memory, it has never been demonstrated that a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 46 publications
6
52
0
1
Order By: Relevance
“…Moreover, others have shown that elevations of GAP-43 protein immunolabeling in the anterior cingulate have been linked to remote memory formation (Maviel et al 2004), and training on a water maze task elevates GAP-43 protein and mRNA expression in the hippocampus compared with swim controls (Pascale et al 2004). GAP-43 heterozygote knockout mice with a 50% reduction in endogenous GAP-43 show impaired retention for a contextual fear-conditioning task (Rekart et al 2005). These data indicate that GAP-43 protein levels prior to behavioral testing can finely calibrate behavioral memory performance, while such performance can then, in turn, In a previous report, both wild-type and G-Phos mice acquired the standard radial arm maze at similar rates.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, others have shown that elevations of GAP-43 protein immunolabeling in the anterior cingulate have been linked to remote memory formation (Maviel et al 2004), and training on a water maze task elevates GAP-43 protein and mRNA expression in the hippocampus compared with swim controls (Pascale et al 2004). GAP-43 heterozygote knockout mice with a 50% reduction in endogenous GAP-43 show impaired retention for a contextual fear-conditioning task (Rekart et al 2005). These data indicate that GAP-43 protein levels prior to behavioral testing can finely calibrate behavioral memory performance, while such performance can then, in turn, In a previous report, both wild-type and G-Phos mice acquired the standard radial arm maze at similar rates.…”
Section: Discussionmentioning
confidence: 99%
“…In addition the neuronal proliferation is also affected (Mani et al 2001;Shen et al 2008). Reflecting these structural defects GAP-43 knockout mice also show functional defects including memory impairment and sensorimotor disorder (Metz and Schwab 2004;Rekart et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the second task employed, contextual fear conditioning (see Rekart et al, 2005, for methods), the G-Perm group (n = 7), in striking contrast to the other groups, showed the highest levels of freezing on Day 21 as well as the best retention scores indicated by the persistently high levels of freezing over the course of subsequent testing (Fig 1B). In contrast, the G-Phos group (n = 9), showed an accelerated rate of extinction differing from the other groups.…”
mentioning
confidence: 99%